Functionality of the nanoscopic crystalline Al/amorphous Al50Ti50 surface embedded composite observed in the NaAlH4 + xTiCl3 system after milling - Pitt, M.; Vullum, P.; Sørby, M.; Sulic, M.; Emerich, H.; Paskevicius, Mark; Buckley, Craig; Walmsley, J.; Holmestad, R.; Hauback, B. (Elsevier B.V., 2012)
The NaAlH4 + xTiCl3 (x < 0.1) system has been studied by a combination of X-ray synchrotron and neutron diffraction, and isotopic H2/D2 scrambling after the completion of the milling process, and the first thermal release of hydrogen (H). An in situ X-ray synchrotron diffraction study of the isochronal release of hydrogen from planetary milled (PM) NaAlH4 + 0.1TiCl3 shows that crystalline (c-) Al1-xTix phases do not form until almost all H is released from the sample, demonstrating that the surface embedded nanoscopic crystalline Al/amorphous (a-) Al50Ti50 composite facilitates the release of H during the very first thermal desorption. Planetary milled (PM) NaAlH4 + xTiCl3 is observed to disproportionate at room temperature, with no NaAlH4 remaining after ca. 200 days. A complete lack of ambient hydrogen release from PM NaAlH4 + 0.1Al (80 nm) measured over 200 days suggests that the nanoscopic a-Al50Ti50 phase is entirely responsible for the hydrogen release during thermal desorption of milled NaAlH4 + xTiCl3. Isotopic H/D exchange has been observed by combined neutron and X-ray synchrotron diffraction on a PM NaAlD4 + 0.04TiCl3 sample, after exposing the milled sample to 20 bar H2 at 50 °C for ca. 6 days. Under these pressure/temperature (P/T) conditions, disproportionation of NaAlD4 is avoided, and ca. 32% of D atoms are exchanged with H atoms. Asymmetrically broadened reflections in the synchrotron data show peak splitting into two unit cell types, one expanded with H, the other remaining close to pure D based unit cell dimensions.The 2-phase model when fitted to the neutron data demonstrates that ca. 56% of D atoms in ca. 58% of all unit cells are exchanged with H, yielding a NaAl(H0.56D0.44)4 composition for the expanded unit cells. HD scrambling (1 bar mixture of H2 and D2 at 23 °C) performed on desorbed H empty PM NaAlH4 + 0.1TiCl3 shows classic H2 + D2 ↔ 2HD equilibrium mixing, demonstrating that nanoscopic Ti containing Al1-xTix surface embedded phases perform a H2 dissociation/recombination function that unadulterated NaAlH4 cannot.